Interleukin-6 as Biomarker for Acute GvHD and Survival After Allogeneic Transplant With Post-transplant Cyclophosphamide - Greco, Raffaella; Lorentino, Francesca; Nitti, Rosamaria; Lupo Stanghellini, Maria Teresa; Giglio, Fabio; Clerici, Daniela; Xue, Elisabetta; Lazzari, Lorenzo; Piemontese, Simona; Mastaglio, Sara; Assanelli, Andrea; Marktel, Sarah; et al. (Frontiers in Immunology, 2019)
Background: Although the outcome of allogeneic hematopoietic stem cell transplantation (allo-HSCT) has dramatically improved in the past decade, it is still compromised by transplant-related mortality (TRM), mainly caused by Graft-versus-Host Disease (GvHD). Methods: We conducted a prospective observational study to ascertain the potential of serum interleukin-6 (IL6) levels, measured before conditioning and 7 days after allo-HSCT, in predicting acute GvHD, TRM and survival after allo-HSCT with Post-Transplant Cyclophosphamide (PT-Cy) based GvHD prophylaxis. Results: Between April 2014 and June 2017, we collected samples from 166 consecutive allo-HSCT patients. By ROC analysis, we identified a threshold of 2.5 pg/ml for pre-transplant IL6 and 16.5 pg/ml for post-transplant IL6. Both univariate and multivariate analyses confirmed the ability of high baseline IL6 levels to predict worse OS (HR 4.3; p <0.01) and grade II-IV acute GvHD (HR 1.8; p 0.04), and of high post-transplant IL6 to identify patients with worse OS (HR 3.3; p <0.01) and higher risk of grade II-IV (HR 5; p <0.01) and grade III-IV acute GvHD (HR 10.2; p <0.01). In multivariate analysis, both baseline (HR 6.7; p <0.01) and post-transplant high IL6 levels (HR 3.5; p 0.02) predicted higher TRM. Conclusions: IL6 may contribute to the risk stratification of patients at major risk for aGvHD and TRM, potentially providing a window for additional prophylactic or preemptive strategies to improve the quality of life in the early post-transplant phase and the outcome of allo-HSCT.